Cognitive Function Characteristics of Parkinson’s Disease with Sleep Disorders - Jing Huang; Wenyan Zhuo; Yuhu Zhang; Hongchun Sun; Huan Chen; Peipei Zhu; Xiaobo Pan; Jianhao Yang; Lijuan Wang (Parkinson's Disease)
Objective. The aim of this study was to investigate the cognitive function characteristics of Parkinson’s disease (PD) with sleep disorders. Methods. Consecutive patients with PD (n=96), patients with primary sleep disorders (n=76), and healthy control subjects (n=66) were assessed. The patients with PD were classified into sleep disorder (PD-SD) and non-sleep disorder (PD-NSD) groups. Results. Among 96 patients with PD, 69 were diagnosed with a sleep disorder. There were 38 sleep disorder cases, 31 RBD cases, and 27 NSD cases. On the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and MoCA subtests, patients in the PD-SD, primary sleep disorder, and PD-NSD groups exhibited lower scores than those in the control group. Moreover, the PD-SD patients exhibited more significant cognitive impairment than was observed in the primary sleep disorder patients. In the PD-SD subgroup, the attention scores on the MoCA and on MoCA subtests were lower in the PD with RBD group than in the PD with insomnia group. Conclusion. PD with sleep disorders may exacerbate cognitive dysfunction in patients. PD associated with different types of sleep disorders differentially affects cognitive functions, and patients with PD with RBD exhibited poorer cognitive function than was seen in patients with PD with insomnia.